The Effect of Institutional Ownership on Firm Value with Tax Avoidance as a Mediating Variable - KAWITRI, Aureola Beatriz; IFADA, Luluk Muhimatul (Journal of Governance, Taxation and Auditing, 2025)
Firm value is crucial for a company because it reflects investor perceptions of the company's performance and prospects, which ultimately impacts share prices and shareholder wealth. Shares owned by institutions can control and minimize agency costs, thereby preventing tax evasion. This study aims to analyze the effect of institutional ownership on firm value, with tax avoidance as a mediating variable. A quantitative approach was specifically used in this research. This quantitative approach was used in this research because the data used are numerical and will be analyzed statistically. This study uses secondary data in the form of documentation, which is obtained and collected indirectly. The study population was food manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Purposive sampling was used to obtain 138 samples. This study utilized secondary data from financial statements. The results showed that institutional ownership had a significant negative effect on firm value, but had no significant effect on tax avoidance. The Sobel test showed that tax avoidance did not mediate the effect of institutional ownership on firm value.